Narratives of resilience in medical students following the 3/11 triple disaster: Using thematic analysis to examine paths to recovery. (October 2020) - Kaye-Kauderer, Halley; Rodriguez, Ana; Levine, Jake; Takeguchi, Yuzo; Machida, Moeko; Feingold, Jordyn; Sekine, Hideharu; Katz, Craig; Yanagisawa, Robert
Highlights: Adolescents represent a resilient population following disasters. Social support and hope for the future contribute to adolescent resilience. Disasters such as 3/11 can positively influence the career paths of survivors. Japanese resilience uniquely relies on luck and suppression of emotions. Abstract: In March of 2011, a 9.0 magnitude earthquake, tsunami, and nuclear explosion damaged northeastern Japan. While nine years have passed, the memory of this disaster continues to linger. This qualitative study had three main goals. First it aimed to explore the reactions and interpretations of adolescents living in areas affected by the disaster. Second, it sought to examine the behaviors and beliefs that enabled these students to not only recover but thrive. Third, it strived to build a more global and dynamic framework of resilience. A convenience sample of 18 students participated in semi-structured face-to-face interviews. Their narratives were qualitatively analyzed using thematic content analysis. Overall, four themes, each with four codes or sub-themes, emerged as sources of resilience including social support (social networks, role models, and community service), hopeful future orientation (cognitive reappraisal, optimism, and motivation to be physician), active emotions (rational compassion, luck, and suppression) and sense of purpose or duty (sharing of personal story, motivation to educate others, and Fukushima image). These findings reveal the experiences of highly resilient youth facing trauma and the connection between childhood adversity and career choices. They also begin to uncover the unique ways that culture, society, and tradition impact processes of recovery.